Política de controle de armas no Brasil (Lei 10.826/2003): direito fundamental à segurança pública como fundamento democrático de limitação ao uso de armas como exercício de liberdade pessoal - Freitas, Maria Juliana Dionisio de (2017)
This thesis presents a study among the political, legal and social fundamentals that legitimate the weapons control policy on Brazil – Law 10.826/2003. First we will situate the reflexes emanated by the political philosophy adopted by a given nation. In this point, the fundamental right to public security develops itself in a constant relation with the right of freedom, proportioning the comprehension of this conflict through the main philosophical and constitutional frameworks, which facilitate the current understanding of the security policies adopted by Brazil. After, understood the need of a harmonic and non-excluding development of the referred fundamental rights (freedom and security), we will analyze more carefully the content served by the right of security through the main national and international legal instruments to, therefore, define its legal nature and meaning as a fundamental right, without prejudice to the study of the most outstanding theories about the application and interpretation of those rights according to the Brazilian doctrine and jurisprudence. In the meantime, will also be identified the implications and mistakes of seeing the weapons control policy as a policy of public security in the control of criminality. At the end, we will present the constitutional, legal and criminological approach of the Statute of Disarming, the unviability of its revocation, the legal and social implications that comes from the possible implantation of a new policy, announced by the project of law 3722/2012, a populist measure which’s being processed in the National Congress. This study is very relevant and makes possible to identify the use of weapons by civilians as the use of a personal freedom that can be restrained by the states apparatus without it being a violation of a fundamental right, on the contrary, it nurtures a space of insecurities and uncertainties able to configure a violation of a legal situation by showing the existence of a serious social kickback, and also, an insufficient protection to people’s rights of life and freedom.